On computation of magnetic fields in closed ring circuits of wind electric power generators - Kussaiynov, K.; Zhakataev, T.A. (Publishing House of the KarSU named after E.A.Buketov, 2014)
The iterative model which allows on induced electro driving force (e.d.f.) is developed. Of an induction of a magnetic field can to calculate numerical values and to define a profile B(y) in in air gap of the electric car. On the basis of it is possible to calculate streams of a magnetic induction F along a ring contour on a stator. The model allows to calculate forces of mechanical coupling of a magnet (on a rotor) with a ferromagnetic material (on a stator) on the basis of calculation of ponderomotive magnetic volume induced forces. The design of the wind generator on the basis of use powerful disk magnets on the basis of an alloy iron–neodymium–boron is developed.
Keywords: iterative model; EMF; magnetic induction; the generator model; circular contour